Assessment of elemental distributions at line and planar defects in Cu(In, Ga)Se2 thin films by atom probe tomography. (15th April 2018) - Cojocaru-Mirédin, Oana; Schwarz, Torsten; Abou-Ras, Daniel
Abstract: Cu(In, Ga)Se2 thin-film solar cells exhibit record power-conversion efficiencies of currently 22.6%. Such performance is impressive in view of the rather small average grain sizes of the Cu(In, Ga)Se2 absorber. This work gives insight to the chemistry at linear and planar defects in Cu(In, Ga)Se2 absorber at the nanometer scale by means of atom-probe tomography. Moreover, the tip sample is investigated by transmission electron microscopy prior to the atom-probe tomography experiments to determine the structure of the planar defects. These experimental results are compared with those from theoretical predictions, and consequences for the energy-band diagrams around these planar defects are proposed. Graphical abstract: Image 1